Characterization of macromolecular lignins as Epstein-Barr virus inducer in foodstuff associated with nasopharyngeal carcinoma risk - Bouvier, Guy; Hergenhahn, Manfred; Polack, A.; Bornkamm, G. W.; de Thé, G.; Bartsch, Helmut (Carcinogenesis, 1995)
Epstein-Barr virus (EBV)-inducing activity was previously demonstrated to occur in various foodstuffs, including dried salted fish in southern China and ‘harissa’, a home made spice mixture in Tunisia, whose consumption is epidemiologically associated with an increased risk for developing nasopharyngeal carcinoma (NPC). For the isolation and the characterization of active ingredients in harissa, we used as a rapid screening assay the induction of the chloramphenicol acetyltransferase (CAT) activity through the EBV-DR promoter in DR-CAT Raji cells. After fractionation of harissa and column chromatography on Sepharose-CL4B, the major inducing activity was associated with a macromolecular fraction which was chemically characterized as lignin-containing complexes. The active material enhanced EBV-DR induction with an activity comparable to the tumor promoter and strong EBV inducer, 12-O-tetradecanoylphorbol-13-acetate. Experiments with inhibitors of protein kinase C-related pathways suggested that the EBV-inducing activity of lignin fractions operates through a different pathway. Our results on the presence of specific lignin fractions in high-risk food items that can induce important cellular functions linked to tumor promotion are discussed in relation to NPC genesis and etiology.
Gesehen am 15.01.2024